Design and Development of an Internal Circulating Hot Air Oven Using the Internet of Things - มิอุบล, ชลทิศ; เรืองศรี, สุรเดช; ดีเจริญชิตพงศ์, จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) design and develop an internal hot air recirculating oven using Internet of Things (IoT) technology, 2) develop a temperature control system to maintain an optimal and stable temperature inside the oven, 3) develop a hot air circulation system to distribute heat evenly, and 4) test and evaluate the performance of the developed system. Conventional drying systems often suffer from inconsistent temperature control and weather dependency. This study developed a system using an ESP32 as the main processing unit, combined with a MAX6675 sensor (K-Type Thermocouple, ±1.5°C, 0-1024°C), controlling four heater-fan units with a total power of 232 watts via 16-channel relays, with real-time monitoring through the Blynk application. Experimental results showed that the developed system maintained the oven temperature within the range of 90-95°C with a standard deviation of ±1.1°C, a maximum temperature difference of 2.3°C across five measurement positions, and reached the target temperature within 35 minutes. The system reduced fruit moisture content from 72.5-88.6% to 18.2-22.3% within 6-9 hours, achieving an average weight reduction of 73.6%. The findings demonstrate that IoT integration with drying systems significantly improves operational efficiency and convenience for household and small-scale industrial applications.